The Oxford Handbook of Poverty and Child Development 2012
DOI: 10.1093/oxfordhb/9780199769100.013.0009
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Parenting: Risk and Protective Factors in the Context of Poverty

Abstract: Adolescent birthrates in the United States are much higher than those in other developed countries, and the majority of adolescents who become mothers come from impoverished backgrounds. Not surprisingly, they experience significant adjustment difficulties, and both their own and their children's developmental outcomes are often compromised. In this chapter, we review the adolescent parenting literature with the goal of uncovering the unique patterns of factors that may enable young mothers to parent successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…The results showed that our nurse home visiting program had a positive effect on parental well-being and maternal parenting as measured by a smartphone eDiary. Previous studies have shown that maternal parenting behaviors in adolescent mothers [ 6 ] and low-income mothers [ 51 , 52 ] are less frequent. Consequently, it was surprising to notice a ceiling effect on some maternal parenting behaviors such as taking care of the child, talking to the child, and playing with the child, regardless of being part of the intervention or control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that our nurse home visiting program had a positive effect on parental well-being and maternal parenting as measured by a smartphone eDiary. Previous studies have shown that maternal parenting behaviors in adolescent mothers [ 6 ] and low-income mothers [ 51 , 52 ] are less frequent. Consequently, it was surprising to notice a ceiling effect on some maternal parenting behaviors such as taking care of the child, talking to the child, and playing with the child, regardless of being part of the intervention or control group.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between adolescent mothers and their children is reported to be different from that of adult mothers. In particular, adolescent mothers have been shown to provide less verbal stimulation and are less sensitive to the child’s needs [ 6 ]. Hence, developing and testing interventions focused on preventing adverse outcomes among this high-risk group is a timely need, especially in LMICs where an estimated 250 million children below the age of 5 do not meet their potential [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent mothers face significant challenges, and both their own and their children’s functioning are often compromised (Grau, Wilson, Weller, Castellanos, & Duran, 2011). In addition to coming from lower socio-economic backgrounds, adolescents who become mothers are more likely to have histories of stressful life events, lower cognitive attainment, and poorer school performance than their non-parenting peers (Hoffman & Maynard, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of explanations have been proposed for the negative associations that have been found between grandmother engagement and the mothers’ parenting. The explanation that has received most research attention suggests the negative effects are due to the increased psychological distress, relationship strain, and/or child-rearing conflicts that arise from the young mothers’ continued, extensive reliance on grandmothers at the same time that they expect increased autonomy from them (Grau et al, 2012). Consistently, mothers whose relationships with grandmothers are low in conflict and high in emotional support or demonstrate a balance in autonomy and mutuality show more competent parenting (Contreras, 2004; Wakschlag, Chase-Lansdale, & Brooks-Gunn, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this cultural background, young Latina mothers are more likely to be in long-term relationships and reside with partners than are African American (AA) and European American (EA) adolescent mothers (Moore, Florsheim, & Butner, 2007; Wasserman, Brunelli, Rauh, & Alvarado, 1994). Moreover, Latina adolescents identify their own mothers (grandmothers) and the children's fathers as the family members most commonly involved in the care of children (Grau, Wilson, Weller, Castellanos, & Duran, 2012). Thus, we sought to understand how their involvement impacted the childrearing context and the children's development.…”
mentioning
confidence: 99%